Targeting Myeloid-Derived Suppressor Cells to Enhance the Antitumor Efficacy of Immune Checkpoint Blockade Therapy - Li, Xueyan; Zhong, Jiahui; Deng, Xue; Guo, Xuan; Lu, Yantong; Lin, Juze; Huang, Xuhui; Wang, Changjun (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells which are activated under pathological conditions, such as cancer and potently support the tumor processes at different levels. Currently, multiple studies have demonstrated that MDSCs induce immune checkpoint blockade (ICB) therapy resistance through their contribution to im-munosuppressive network in the tumor microenvironment. In addition, non-immunosuppressive mechanisms of MDSCs such as promotion of angiogenesis and induction of cancer stem cells also exert a powerful role in tumor progression. Thus, MDSCs are potential therapeutic targets to enhance the anti-tumor efficacy of ICB therapy in cases of multiple cancers. This review focuses on the tumor-promoting mechanism of MDSCs and provides an overview of current strategies that target MDSCs with an objective of enhancing the anti-tumor efficacy of ICB therapy.